The relationship between the burnout and organizational commitment levels of the police officers’ : a research on Istanbul police headquarters - Arı, Samet (My University, 2011)
Bu araştırmanın amacı, polis memurlarının tükenmişlik ve örgütsel bağlılık düzeyleri arasındaki ilişkiyi belirlemektir. Bu amaca ulaşmak için, tükenmişlik ve örgütsel bağlılık literatür taraması yapılarak farklı boyutlarıyla incelendi. Bu çalışmada polis memurlarının bağımsız değişken olan tükenmişlik düzeyleri ile ilgili bilgiler, Maslach ve Jackson (1981) tarafından geliştirilen ve Ergin (1993) tarafından Türkçe‘ye uyarlanan Maslach Tükenmişlik Envanteri ile toplanmıştır. Bağımlı değişken olan örgütsel bağlılık Meyer ve Allen (1991) tarafından geliştirilen Örgütsel Bağlılık Anketi aracılığı ile toplanmıştır. Kişisel bilgiler için Kişisel Bilgi Formu kullanılmıştır. Bu araştırma İstanbul Emniyet Müdürlüğü Boğaziçi Köprüleri Koruma Şube Müdürlüğü’nde görevli 112 polis memuru üzerinde yapılmıştır. Veriler Pearson korelasyon katsayısı, doğrusal regresyon, bağımsız örneklem t-testi ve tek yönlü varyans analizi (ANOVA) ile analiz edilmiştir. Analiz sonucunda, polis memurlarının tükenmişlik ve örgütsel bağlılık düzeyleri arasında anlamlı negatif bir ilişki bulunmuştur. Duygusal Tükenmişlik, Normatif bağlılık ve Devam bağlılığı ile anlamlı negatif bir ilişki göstermiştir. Duyarsızlaşma ile Normatif bağlılık arasında anlamlı negatif düşük düzeyde bir ilişki bulunmuştur. Ayrıca Kişisel Başarı ve Duygusal bağlılık arasında anlamlı negatif bir ilişki bulunmuştur. Ayrıca regresyon analizinin sonuçlarına göre Duygusal, Normatif ve Devam bağlılığının duygusal tükenme, duyarsızlaşmavekişiselbaşarıtarafındananlamlıolarakyordandığıbulunmuştur. Araştırmaya katılan polis memurlarının tükenmişlik ve örgütsel bağlılık düzeyleri yaş, medeni durum, kıdem, görev yeri, çalışma süresi, disiplin cezası, ödül ve soruşturma gibi değişkenler açısından karşılaştırılmıştır. Polis memurlarının Disiplin cezası ve Ödül değişkenleri ile örgütsel bağlılık düzeyleri arasında anlamlı bir farklılık bulunmuştur. Polis, Tükenmişlik, Örgütsel Bağlılık

The aim of this research is to determine the relationship between the burnout and organizational commitment levels of the police officers’. To reach this aim, burnout and organizational commitment were examined from different dimensions and literature review was done. The information concerning the burnout levels of police officers’, which served as the independent variable, was collected by using Maslach Burnout Inventory (developed by Maslach and Jackson, 1981), adapted Turkish by Ergin (1993). The information concerning the organizational commitment, which served as the dependent variable in this research was collected through Organizational Commitment Questionnaire (developed by Meyer and Allen, 1991) and for personal information Personal Information Form were used. This research was conducted on 112police officers on Bosphorus Bridges Guarding Directorate (BBGD) in Istanbul. Data was analyzed by pearson correlation coefficient, linear regression, independent sample t-test and one-way analysis of variance (ANOVA). As a result of analysis, there was found a significant negative relationship between burnout and organizational commitment levels of the police officers’. There was a significant negative relationship among Emotional Exhaustion with Normative Commitment and Continuance Commitment. It was found Depersonalization showed a significant negative slightly relationship with Normative Commitment. And also there was found a significant negative relationship between Personal Accomplishment and Affective Commitment. Besides with the results of regression analysis, Emotional exhaustion, Depersonalization and Personal accomplishment are significant predictor of Affective, Normative and Continuance commitment. Also police officers were compared burnout and organizational commitment levels according to age, marital status, tenure, department, work experience, disciplinary punishment, rewarded and Inquiry variables. Among organizational commitment level with Disciplinary Punishment and Rewarded variables were found a significant difference of the police officers’. Police, Burnout, Organizational Commitment.
Keywords: Örgütsel Bağlılık; Tükenmişlik